PENGARUH KUALITAS PRODUK PROMOSI DAN PERSAINGAN TERHADAP VOLUME PENJUALAN DI SUSUKU CAFÉ UNGARAN - Andi Saputra; Nunuk Supraptini; Fajar Suryatama (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Today's business development is growing very rapidly. Every business actor in each business unit is required to always have sensitivity to changes that occur One of the business sectors that is experiencing a significant decline, in January the total income was 84% then in July it became 80%, due to the month that it was implemented the large-scale social restriction (PSBB) policy by the government Another factor influencing the decline in sales is the emergence of many competitors from similar companies. The problem in this study is to determine the effect of product quality, promotion and competition on sales volume, either partially or simultaneously. The type of research used is explanatory research. The population in this study were all visitors to Susuku Café Ungaran who made purchases whose amount is not known with certainty. With the sampling technique used, namely unknown populations, the research sample obtained is 100 respondents. The results of multiple regression analysis for the variable product quality to sales volume obtained tcount 3.620, promotion to sales volume obtained tcount 3.187 and competition to sales volume obtained tcount 7110. Based on the Fcount test, the Fcount value is 39,052. The results of the study can be concluded that the variables of product quality, promotion and competition have a partial effect. Product quality, promotion and competition variables simultaneously affect the sales volume at Susuku Café Ungaran